Little women, or, Meg, Jo, Beth, and Amy - Alcott, Louisa May. 1832-1888. (Naples, FL : Trident Press International, 2000)
Chronicles the joys and sorrows of the four March sisters as they grow into young women in mid-nineteenth-century New England.
Keywords: Sisters -- Fiction; Family life -- New England -- Fiction; New England -- History -- 19th century -- Fiction